2018
DOI: 10.31018/jans.v10i4.1897
|View full text |Cite
|
Sign up to set email alerts
|

A review on zinc and boron nutrition in rice

Abstract: Micronutrients, though needed in smaller amounts, play a major role in the production and productivity of rice. Zn is the fourth most deficient nutrient element in Indian soils and its deficiency causes severe yield reduction in rice. Application of Zn either as foliar spray or soil application caused significant improvement in growth and yield attributes and yield of rice. Similar to that of Zn, B nutrition also caused significant improvement in growth and yield attributes and yield of rice. The review elabor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…This effect is due to the large role played by the zinc element in supporting the growth and yield of crops, especially rice, this role is increased when enriched with the zinc element, especially in the poor soil of this element, as in most of the Egyptian soils. Ali et al (2016) reported that zinc deficiency is a barrier in achieving higher rice yield when they found that the highest rice growth parameters and yield were obtained with applying 14 kg ZnSO 4 .7H 2 O ha -1 , this result is close to (Farooq et al 2016) who reported that all Zn application methods increased grain yield of rice by around 30% compared with the control (no added Zn), while (Suman and Sheeja 2018) have recognized that zinc deficiency causes severe yield reduction in rice, so the application of Zn such as foliar or soil application caused significant improvement in growth and yield attributes and yield of rice.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…This effect is due to the large role played by the zinc element in supporting the growth and yield of crops, especially rice, this role is increased when enriched with the zinc element, especially in the poor soil of this element, as in most of the Egyptian soils. Ali et al (2016) reported that zinc deficiency is a barrier in achieving higher rice yield when they found that the highest rice growth parameters and yield were obtained with applying 14 kg ZnSO 4 .7H 2 O ha -1 , this result is close to (Farooq et al 2016) who reported that all Zn application methods increased grain yield of rice by around 30% compared with the control (no added Zn), while (Suman and Sheeja 2018) have recognized that zinc deficiency causes severe yield reduction in rice, so the application of Zn such as foliar or soil application caused significant improvement in growth and yield attributes and yield of rice.…”
Section: Discussionmentioning
confidence: 60%
“…Compost tested greatly useful in enhancing the yield of the rice crop and N uptake (Satyanarayana et al 2002;Khafagy et al 2017). While (Suman and Sheeja 2018) have recognized that zinc deficiency causes severe yield reduction in rice, so the application of Zn such as foliar or soil application caused significant improvement in growth and yield attributes and yield of rice. Also, El-Hadidi et al (2016) and Kafagy et al (2017) who found that zinc fertilizer had a positive effect on rice dry matter production, plant height yield and nitrogen uptake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Micronutrients play a role in increasing crop productivity and grain yields as a result of improving plant enzymatic systems [22]. Suman and Sheeja [23] reported that the foliar application of Zn micronutrients in rice played a role in increasing growth and yield of rice.…”
Section: Resultsmentioning
confidence: 99%
“…Devi et al, 2019 reported that higher growth and yield parameters were observed by transplanting 2-3 seedlings with age of 15 days. Suman and Sheeja (2018) revealed that, application of Zinc either as foliar spray or soil application caused significant improvement in growth and yield attributes and yield of rice. Khan et al, (2002) reported similar results.…”
Section: Effect Of Integrated Crop Management On Growth and Yield Parameters Of Paddymentioning
confidence: 99%